sage: assume(x,'real')
sage: solve(exp(x)+exp(-1/2*x) == 2,x)
[x == 2*log(1/2*sqrt(5) - 1/2), x == 0]
that ist ok!

how can i get here the solution x==0?
sage: solve(exp(x)+exp(1/2*x) == 2,x)
[e^x == -e^(1/2*x) + 2]

Thanks for help.

1 | initial version |

sage: assume(x,'real')
sage: solve(exp(x)+exp(-1/2*x) == 2,x)
[x == 2*log(1/2*sqrt(5) - 1/2), x == 0]
that ist ok!

how can i get here the solution x==0?
sage: solve(exp(x)+exp(1/2*x) == 2,x)
[e^x == -e^(1/2*x) + 2]

Thanks for help.

2 | formatting |

```
sage: assume(x,'real')
sage:
```~~solve(exp(x)+exp(-1/2~~*x) **solve(exp(x)+exp(-1/2*x) == 2,x)
[x == *~~2~~log(1/2*sqrt(5) 2*log(1/2*sqrt(5) - 1/2), x == 0]

that ist ok!

how can i get here the solution ~~x==0?
~~x==0?

`sage: `~~solve(exp(x)+exp(1/2~~*x) **solve(exp(x)+exp(1/2*x) == 2,x)
[e^x == *~~-e^(1/2~~x) -e^(1/2*x) + ~~2]~~2]

Thanks for help.

Copyright Sage, 2010. Some rights reserved under creative commons license. Content on this site is licensed under a Creative Commons Attribution Share Alike 3.0 license.